Three-dimensional impact-angle-constrained cooperative guidance strategy against maneuvering target - You, Hao; Chang, Xinlong; Zhao, Jiufen; Wang, Shunhong; Zhang, Youhong (ISA transactions, 2023)
In order to improve the multiple-missile cooperative attack capability and penetration capability, this paper investigates two three-dimensional impact-angle-constrained cooperative guidance strategies against maneuvering target for controllable thrust missiles. First, a three-dimensional nonlinear guidance model is established that does not assume small missile lead angles in the guidance process. Second, in the line-of-sight (LOS) direction of the cluster cooperative guidance strategy, the proposed guidance algorithm transforms the simultaneous attack problem into a second-order multiagent consensus problem, which effectively solves the practical problem of low guidance precision provoked by the time-to-go estimation. Then, by combining second-order sliding mode control (SMC) and nonsingular terminal SMC theory, the guidance algorithms in the normal and lateral directions to the LOS are designed, respectively, so that the multi-missile can accurately attack a maneuvering target while satisfying the impact angle constraints. Finally, by utilizing the second-order multiagent consensus tracking control in the leader-following cooperative guidance strategy, a novel leader-following time consistency algorithm is investigated to ensure that the leader and followers can attack the maneuvering target simultaneously. Moreover, the stability of the investigated guidance algorithms is proved mathematically. The effectiveness and superiority of the proposed cooperative guidance strategies are verified by numerical simulations. •This paper designs two three-dimensional impact-angle-constrained cooperative guidance strategies against maneuvering target.•This paper utilizes the relative distance and radial relative velocity as consensus variables to improve guidance precision.•This paper combines a nonsingular SMC with a second-order sliding mode control theory to improve guidance performance.•The proposed cooperative guidance algorithm has a simpler form and a more straightforward structure to avoid singularity problems.